PENERAPAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VII/2010 TERHADAP KEWARISAN ANAK LUAR NIKAH (STUDI PUTUSAN PERADILAN AGAMA) - MUHAMMAD FAUZI SYAYREZA (PREMISE LAW JURNAL, 2017)
The Constitutional Court's decision on the status of children given birth outside of mating, where there is a legal status and inheritance relation illegitimate child after the birth of this decision. The Constitutional Court mean that children born out of wedlock obtain adequate legal protection, because in principle, the child is not guilty because of his birth against their will. Children who are born without a father have a clear status often receive unfair treatment and stigma in the society. Law should provide protection and legal certainty to the status of a child born and rights available to him, including against children born though the validity of the marriage is still disputed.Keywords: Implementation, Inheritance, Illegitimate Children.